Zaldivar Ovalle, María Inés. (ed.), Francisco de Borja y Aragón, Príncipe de Esquilache. Relación y sentencia del virrey del Perú (1615-1621). New York: IDEA, 2016. 270pp. ISBN, ISBN: 978-1-938795-25-1. - Salazar Lisboa, Eric Francisco (Acta Literaria, 2019)